The impact of fragile X premutation carrier status on embryo morphokinetic development. Issue 5 (November 2022) - Shulman, Yael; Kalma, Yael; Malcov, Mira; Kopel, Rotem; Fouks, Yuval; Azem, Foad; Almog, Benny; Cohen, Yoni
Abstract: Research question: Does inheritance of the fragile X mental retardation 1 (FMR1) premutation allele affect embryo morphokinetic development? Design: A retrospective cohort analysis of 529 embryos from 126 IVF cycles of 39 FMR1 premutation female carriers undergoing preimplantation genetic testing for monogenic/single gene defects (PGT-M). Morphological and morphokinetic parameters obtained using a time-lapse monitoring system were compared between embryos that inherited the FMR1 premutation allele (FMR1 group, n = 271) and those who received the normal allele (normal group, n = 258). The following embryo outcome measures were compared: morphokinetic parameters up to day 3, start of blastulation time (tSB) for day 5 embryos and the rate of top-quality embryos on days 3 and 5. Results: No differences were found in morphokinetic parameters between the groups from the time of intracytoplasmic sperm injection (ICSI) until a biopsy on day 3. The blastulation rate in the two groups was comparable. However, the start of blastulation was delayed in FMR1 embryos compared to that in the genetically normal embryos (median tSB: 104.2 h [99.3−110.3] versus 101.6 h [94.5−106.7], P = 0.01). In addition, the rate of top-quality FMR1 embryos was lower than that of genetically normal embryos (25.6% versus 38.8%, P = 0.04). Conclusion: Embryos that inherit the FMR1 premutation allele are of lower quality at the blastocyst stage compared with those that do not inherit the mutated allele.